Extending the mind: a review of ethnographies of neuroscience practice - Mahfoud, Tara (Frontiers in Human Neuroscience, 2014)
This paper reviews ethnographies of neuroscience laboratories in the United States and Europe, organizing them into three main sections: 1) descriptions of the capabilities and limitations of technologies used in neuroimaging laboratories to map ‘activity’ or ‘function’ onto structural models of the brain, 2) discussions of the ‘distributed’ or ‘extended’ mind in neuroscience practice, and 3) the implications of neuroscience research and the power of brain images outside the laboratory. I will try to show the importance of ethnographic work in such settings, and place this body of ethnographic work within its historical framework - such ethnographies largely emerged within the Decade of the Brain, as announced by former President of the United States George H. W. Bush in 1990. The main argument is that neuroscience research and the context within which it is taking place has changed since the 1990’s - specifically with the launch of ‘big science’ projects such as the Human Brain Project in the European Union and the BRAIN initiative in the United States. There is an opportunity for more research into the institutional and politico-economic context within which neuroscience research is taking place, and for continued engagement between the social and biological sciences.